Curating Oral Histories : From Interview to Archive. - MacKay, Nancy (Left Coast Press, 2006)
Written in a practical, instructive style, MacKay goes carefully through the various steps that take place after the oral history interview--transcribing, cataloging, preserving, archiving, and making your study accessible to others.